PENGARUH KREATIVITAS SISWA TERHADAP KESULITAN BELAJAR DI SMP RK DELI MURNI DELI TUA TAHUN AJARAN 2020/2021 - Khairunisa Hidayati; Widya Utami Lubis (Genta Mulia : Jurnal Ilmiah Pendidikan, 2022)
AbstractThis study aims to: (1) To determine the effect of student creativity on learning difficulties in SMP RK Deli Murni Deli Tua. The research used is a research using a quantitative approach. The subjects of this study were 27 7th grade students of SMP RK Deli Murni Deli Tua. In this study, various instruments were used to collect data such as: (1) Student creativity questionnaire (2) Student learning difficulties questionnaire. The results of this study are (1) There is a significant influence between students' creativity on learning difficulties at SMP RK Deli Murni Deli Tua. Kata kunci: Influence,Student Creativity, Learning Difficulties